Prefrontal Cortex Activity Predicts Mental Fatigue in Young and Elderly Men During a 2 h “Go/NoGo” Task - Terentjeviene, Asta; Maciuleviciene, Edita; Vadopalas, Kazys; Mickeviciene, Dalia; Karanauskiene, Diana; Valanciene, Dovile; Solianik, Rima; Emeljanovas, Arunas; Kamandulis, Sigitas; Skurvydas, Albertas (Frontiers in Neuroscience, 2018)
Background. Although the effects of mental fatigue on cognitive–motor function and psychological state in young adults are well documented, its effects in the elderly are not completely understood. The aim of this study was to estimate the effect of prolonged cognitive load on the indicators of psychological, cognitive, and motor functions. Methods. Fifteen young and 15 elderly men were asked to perform a 2 h “Go/NoGo” task. Psychological state (mood and motivation), cognitive (prefrontal cortex activity and cognitive performance), and motor (motor cortex excitability and grip strength) functions were measured before and after the task. During the 2 h task, both groups had a significantly similar increase in the number of “Incorrect NoGo” errors. Only in young men reaction time (RT) of “Incorrect NoGo” and intraindividual variability of RT of “Incorrect NoGo” significantly increased during task. After the task, handgrip strength decreased for the young men, whereas latency of motor evoked potentials prolonged both groups. Nevertheless, both groups indicated that they felt fatigue after the 2 h task; we observed that mental demand increased, whereas intrinsic motivation and mood decreased only in young men. Prolonged task decreased the switching/rest ratio of oxygenated hemoglobin for the young and the elderly men; however, greater for elderly than young men. Interestingly, the more the prefrontal cortex was activated before the 2 h task during the switching task, the fewer of “Incorrect NoGo” errors made by the young men and the greater the number of errors made by the elderly men. Conclusion. Because of the greater mental load and (possibly) greater activation of prefrontal cortex during the 2 h “Go/NoGo” task, there was greater mental and neuromuscular performance fatigue in young men than in elderly men.